Familial Mediterranean fever-related miR-197-3p targets IL1R1 gene and modulates inflammation in monocytes and synovial fibroblasts - Yeliz Z. Akkaya-Ulum (Nature Portfolio, 2021)
Abstract Familial Mediterranean fever (FMF); is an autosomal recessively inherited autoinflammatory disease caused by the mutations in the Mediterranean Fever (MEFV) gene. Recent studies have shown that epigenetic control mechanisms, particularly non-coding RNAs, may play a role in the pathogenesis of autoinflammation. microRNAs (miRNAs) are small non-coding RNAs that play critical roles in regulating host gene expression at the post-transcriptional level. The phenotypic heterogeneity of FMF disease suggests that FMF may not be a monogenic disease, suggesting that epigenetic factors may affect phenotypic presentation. Here we examined the potential anti-inflammatory effect of miR-197-3p, which is a differentially expressed miRNA in FMF patients, by using inflammation related functional assays. We monitored gene expression levels of important cytokines, as well as performed functional studies on IL-1β secretion, caspase-1 activation, apoptosis assay, and cell migration assay. These experiments were used to evaluate the different stages of inflammation following pre-miR-197 transfection. Anti-miR-197 transfections were performed to test the opposite effect. 3′UTR luciferase activity assay was used for target gene studies. Our results obtained by inflammation-related functional assays demonstrated an anti-inflammatory effect of miR-197-3p in different cell types (synovial fibroblasts, monocytes, macrophages). 3′UTR luciferase activity assay showed that miR-197-3p directly binds to the interleukin-1beta (IL-1β) receptor, type I (IL1R1) gene, which is one of the key molecules of the inflammatory pathways. This study may contribute to understand the role of miR-197-3p in autoinflammation process. Defining the critical miRNAs may guide the medical community in a more personalized medicine in autoinflammatory diseases.